2013
DOI: 10.1128/jvi.02629-13
|View full text |Cite
|
Sign up to set email alerts
|

Activation of the Endoplasmic Reticulum Calcium Sensor STIM1 and Store-Operated Calcium Entry by Rotavirus Requires NSP4 Viroporin Activity

Abstract: Rotavirus nonstructural protein 4 (NSP4) induces dramatic changes in cellular calcium homeostasis. These include increased endoplasmic reticulum (ER) permeability, resulting in decreased ER calcium stores and activation of plasma membrane (PM) calcium influx channels, ultimately causing a 2-to 4-fold elevation in cytoplasmic calcium. Elevated cytoplasmic calcium is absolutely required for virus replication, but the underlying mechanisms responsible for calcium influx remain poorly understood. NSP4 is an ER-loc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
60
0
2

Year Published

2014
2014
2018
2018

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 66 publications
(67 citation statements)
references
References 45 publications
(76 reference statements)
5
60
0
2
Order By: Relevance
“…Basically, the viral ER-anchored glycoprotein NSP4, a pore-forming viroporin, elicits the leakage of Ca 21 from the ER to the cytosol. This ion mobilization, in turn, activates autophagy through the CaMKK2-AMPK pathway; CaMKK2 inhibition by (Hyser et al, 2013). Later, the rotavirus also interferes with autophagy membrane trafficking to transport viral ER-associated proteins to sites of genome replication and particle assembly since lower expression of ATG3 and ATG5 highly reduce virus yield.…”
Section: Crosstalk Between Ca 21 and Autophagy In Infection And Inflamentioning
confidence: 99%
“…Basically, the viral ER-anchored glycoprotein NSP4, a pore-forming viroporin, elicits the leakage of Ca 21 from the ER to the cytosol. This ion mobilization, in turn, activates autophagy through the CaMKK2-AMPK pathway; CaMKK2 inhibition by (Hyser et al, 2013). Later, the rotavirus also interferes with autophagy membrane trafficking to transport viral ER-associated proteins to sites of genome replication and particle assembly since lower expression of ATG3 and ATG5 highly reduce virus yield.…”
Section: Crosstalk Between Ca 21 and Autophagy In Infection And Inflamentioning
confidence: 99%
“…Well-described viroporins are known from influenza virus, HIV, picornaviruses, rotaviruses, coronaviruses, and others, while putative viroporins have been reported for many other viruses (18,19,(38)(39)(40). Viroporins can act intracellularly to permeabilize organelle membranes (41), modulate calcium homeostasis (42), alter organelle acidification (43), induce autophagy (44), and otherwise "customize host cells for efficient viral propagation" (41). Other viroporins may act extracellularly and permeabilize infected or noninfected cells (18).…”
Section: Abstract Delta Peptide Ebola Virus Enterotoxins Permeabilmentioning
confidence: 99%
“…Another study suggested that NSP4 protein translocated to mitochondria, disrupts its membrane potential and elicits intrinsic apoptotic pathway [27]. However, it has been indicated that enterotoxin and viroporin activity of the NSP4 protein mediates increased ER permeability, resulting in decreased ER calcium stores and dramatically increase in cytosolic Ca2+ concentration [28]. On the other hand, depletion of ER Ca2+, for any reason, causes ER stress that often triggers a UPR signaling leading to apoptosis [29].…”
Section: Discussionmentioning
confidence: 98%